Answer:
C
Step-by-step explanation:
Calculate the distance (d) using the distance formula
d = √ (x₂ - x₁ )² + (y₂ - y₁ )²
with (x₁, y₁ ) = (2, 8) and (x₂, y₂ ) = (- 1, 9)
d = [tex]\sqrt{(-1-2)^2+(9-8)^2}[/tex] = [tex]\sqrt{(-3)^2+1^2}[/tex] = [tex]\sqrt{9+1}[/tex] = [tex]\sqrt{10}[/tex] → C
Answer:
[tex]\sqrt{10}[/tex]
Step-by-step explanation:
Using the distance formula:
[tex]\sqrt{(x_b - x_a)^2 + (y_a - y_b)^2}[/tex]
Plugging the numbers in:
[tex]\sqrt{(-1-2)^2 + (9 - 8)^2 }[/tex]
Simplify:
[tex]\sqrt{9 + 1}[/tex]
Answer:
[tex]\sqrt{10}[/tex]
If you found this useful be sure to rate and give brainliest :)
^.^
Amanda